Influence of bitumen and aggregate polarity on interfacial adhesion - Baldi Sevilla, Alejandra (2017)
The quality of the bitumen–aggregate interface formed in an asphalt mixture is dictated by the physicochemical properties of both materials, such as surface polarity. In order to better understand the role of polarity on interfacial adhesion between bitumen and aggregate, a systematic study was conducted by designing bitumens with different polarities. These bitumens were produced by the addition of diatoms and hydrophobic diatoms in varying concentrations. It was found that by manipulating the polarity of bitumen it is possible to design materials that result in bitumen–aggregate pairs that are more compatible with each other and resistant to debonding. On the other hand, basicity of aggregates is also highly related to obtaining asphalt mixtures with improved durability. The findings from this paper help advance the fundamental understanding of the adhesive behaviour between bitumens and aggregates. More importantly, these findings can be used to design optimal anti-strip agents for using in different asphalt mixtures.